2007
DOI: 10.1159/000098364
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Therapy in <i>Helicobacter pylori</i>-Positive Patients with Halitosis: Long-Term Outcome

Abstract: Objective: The aim of this study was to investigate the incidence and long-term outcome of halitosis before and after eradication therapy in patients with functional dyspepsia and Helicobacter pylori infection. Subjects and Methods: Halitosis and dyspepsia-related symptoms were investigated by way of a questionnaire. Only patients with functional dyspepsia, H. pylori infection and no histological evidence of atrophy were included in the study. A total of 18 patients fulfilled these criteria and completed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
3
35
0
4
Order By: Relevance
“…http://ginsengres.org ment of halitosis with eradication of H. pylori [44,45]. Lee et al [46] first reported production of VSCs by H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…http://ginsengres.org ment of halitosis with eradication of H. pylori [44,45]. Lee et al [46] first reported production of VSCs by H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack of critical evidence that associates gastrointestinal disease with halitosis except for a Helicobacter pylori infection [6,7,8], which does have some links to halitosis symptoms. Lee et al [6] showed that H. pylori directly produced volatile sulfur compounds (VSCs) with the addition of cysteine in culture media and Katsinelos et al [9] reported that the eradication of H. pylori in patients with functional dyspepsia led to a sustained resolution of halitosis during long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, some studies revealed that halitosis was quite prevalent in H. pylori positive group and others showed that halitosis was improved after the eradication therapy of H. pylori. [6][7][8][9][10] H. pylori infection was responsible for volatile sulfur compounds (VSCs) production, known as causative constituents of halitosis. VSCs, composed of hydrogen sulfide, methyl mercaptan, and dimethyl sulfide, have been known as the main factor of halitosis.…”
Section: Introductionmentioning
confidence: 99%